Blockchains for Network Security : Principles, technologies and applications - Huang, Haojun; Wang, Lizhe, 1974-; Wu, Yulei; Choo, Kim-Kwang Raymond (IET computing series ;, 2020)
The book comprises 12 chapters dealing with the following subjects: blockchains for network security; blockchain system architecture; blockchain consensus and incentives; Internet of Things; 5G and 6G networks; edgechain for organization-based multi-agent systems; privacy-preserving machine learning; smart metering; sharding; GIS; and remote sensing big data management and production